2019
DOI: 10.1002/ece3.5728
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression response to a nematode parasite in novel and native eel hosts

Abstract: Invasive parasites are involved in population declines of new host species worldwide. The high susceptibilities observed in many novel hosts have been attributed to the lack of protective immunity to the parasites which native hosts acquired during their shared evolution. We experimentally infected Japanese eels (Anguilla japonica) and European eels (Anguilla anguilla) with Anguillicola crassus, a nematode parasite that is native to the Japanese eel and invasive in the European eel. We inferred gene expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 89 publications
(181 reference statements)
1
20
0
Order By: Relevance
“…We hypothesized that encapsulation in a natural population may trigger an immune response and lead to increased expression of mhc II genes. Cox1 expression was reduced in European eels experimentally infected with A. crassus (Bracamonte, Johnston, Monaghan, et al., 2019). We hypothesized that the disruption of the energy balance would be mitigated by encapsulation, resulting in higher expression of cox1 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized that encapsulation in a natural population may trigger an immune response and lead to increased expression of mhc II genes. Cox1 expression was reduced in European eels experimentally infected with A. crassus (Bracamonte, Johnston, Monaghan, et al., 2019). We hypothesized that the disruption of the energy balance would be mitigated by encapsulation, resulting in higher expression of cox1 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with higher oxygen demand with infection severity, the expression of the haemoglobin α gene was correlated with parasite biomass in experimental infections (Fazio et al., 2009). Down‐regulation of several cytochrome genes of the cell respiration pathway indicated that energy provision may be compromised in experimentally infected European eels, which may be due to alteration of resource allocation in infected individuals (Bracamonte, Johnston, Monaghan, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, driven by declining costs, RNA-seq is becoming increasingly accessible to labs with modest resources; and as a result, it is being employed on an everexpanding catalog of non-model organisms, pervading the fields of agriculture, aquaculture, ecology, and environment. A very short list of recent studies include: environmental stress response in sea-trout [3], coral [4], ryegrass [5], pigeonpea [6], tiger barb [7]; immune response to parasites and pathogens in guppy [8], eel [9], silkworm [10], peanut [11], sunflower [12]; mechanisms of phenotypic divergence in hares [13], bats [14], grass carps [15]; effect of diet in the growth and development in shrimp [16], yellow perch [17], mandarin fish [18], grenadier anchovy [19], catfish [20], tilapia [21], bass [22]. It is only likely that RNA-seq will continue to rapidly proliferate while high-quality reference databases grow at a slow pace.…”
Section: Introductionmentioning
confidence: 99%